Sposoby finansowania innowacji w Polsce i wybranych krajach Unii Europejskiej - Pohulak-Żołędowska, Elżbieta (Innovation' Financing in Poland and Chosen EU Countries, 2007)
In this article, the author tries to show the problem of innovation in European enterprises in the context of shortage of capital given to R&D purposes. The R&D expenditures are the key problem in conducting and implementation of R&D results to the enterprises. They are also the base in inducing the knowledge-based economy to modern European market economies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 66-78